Mitochondrial structure and function in OCRL depleted cells - Philip, Ron George; Bhatia, Priyanka; Sharma, Yojet; Raghu, Padinjat (Frontiers in Cell and Developmental Biology, 2025)
Lowe syndrome (LS) is an X-linked, recessive disease with a characteristic clinical triad of eye, brain, and kidney defects. LS results from mutations in the OCRL gene that encodes for inositol polyphosphate 5-phosphatase enzyme. The OCRL protein has been localized to multiple subcellular organelles including the plasma membrane and endo-lysosomal system, but the relevance of these to disease phenotypes is unclear. Previous studies have reported severe hypotonia at birth in LS patients along with structural changes in the mitochondria in muscle biopsies. These mitochondrial changes have been proposed to be secondary to renal tubular acidosis seen in LS patients. In this study, we find that neural stem cells and neurons differentiated from OCRL-depleted induced pluripotent stem cells (iPSCs) show mild defects in mitochondrial structure and function, whereas such defects are not seen in the iPSCs themselves. These mitochondrial phenotypes in neural stem cells and neurons were associated with modest changes in the mitochondrial transcriptome. Overall, our results indicate that loss of OCRL leads to mild cell autonomous defects in mitochondrial structure and function that is cell type-dependent.